PENDEKATAN OPSI CASH-OR-NOTHING UP AND IN BARRIER UNTUK PENENTUAN NILAI PREMI ASURANSI PERTANIAN - Yunita Wulan Sari; Gunardi Gunardi (Indonesian Journal of Statistics and Applications, 2020)
Crop insurance is a type of insurance that provides protection to farmers who hold an insurance policy for losses due to crop failure. Extreme weather, especially rainfall, has been the main cause of the crop failure. Therefore, the type of crop insurance based on weather or rainfall must be developed and applied. This paper will discuss the cash-or-nothing up and in barrier option approach for determining insurance premiums where the risk of loss in terms of high rainfall, then compare it to the Black-Scholes option approach. In this approach, the claim limit is based on the rainfall index and the value of the barrier is determined according to the size of the extreme rainfall. We use cumulative rainfall data in the first subround in Sleman regency as a case study. The conclusions obtained are barrier value has a negative effect on the value of insurance premiums and claim limit value has a positive effect. Besides the premium value with this barrier option approach is cheaper than the Black-Scholes option approach, this approach method more interesting to apply because of the barrier value addition.